Cost Effective Automated Street Lighting Control - Jinwen Zhu; Christopher Raison (Institute of Advanced Engineering and Science, 2014)
Roads and their lighting systems are important facilities of local municipals. Most conventional street lighting systems are switched on/off at regular intervals of time. The consequence is that a large portion of electrical energy consumed by the street lighting is wasted meaninglessly if the road traffic is low. With the increasing interest in the global energy consumption and green environment requirement, automated street lighting system raises much interest around the world. In this paper, a cost effective and energy efficient automated street light control based on microcontroller and ZigBee wireless network is proposed. The street lamps are automatically controlled with the ambient light conditions, the road pedestrian and vehicle traffic conditions, and the neighbor traffic conditions.DOI:http://dx.doi.org/10.11591/ijece.v4i5.6446